PENGARUH FASILITAS DAN KUALITAS PELAYANAN TERHADAP KEPUASAN NASABAH DI PT BPR INDOBARU FINANSIA - wani, Sari; Mardika, Nanda Harry (SCIENTIA JOURNAL, 2021)
This study aims to examine the effect of facilities and service quality on customer satisfaction at PT BPR Indobaru Finansia in Batam. This study uses a quantitative approach and nonprobability sampling techniques with purposive sampling method. The data collection technique used a questionnaire with a Likert scale which was filled in by 171 respondents. Data analysis used SPSS version 25. The results of the facility variable test were obtained with tcount (6.565)> t table (1.653) and a significance value of 0.000 f table 3.05 and a significant value of 0.000 or less than 0.05 (F. Sig 0.000 <α 0.005). So it can be concluded that the facilities and service quality partially and simultaneously have a significant effect on customer satisfaction at PT BPR Indobaru Finansia in Batam. The test results of the coefficient of determination have 51.3%. The remaining 48.7% is influenced by other variables not in this study.